ANALISIS KINERJA EKSPOR OLAHAN KAKAO INDONESIA DI PASAR GLOBAL - Hariri, Rif'an (Universitas 17 Agustus 1945 Semarang, 2025)
Cocoa fruit is one of the crops with a long history in Indonesia. Cocoa powder and chocolate are among the export commodities processed from cocoa fruit. Currently, cocoa product exports fluctuate annually. The challenges faced in cocoa product exports are diverse. This study aims to analyze the performance of cocoa product exports in the global market. The data used in this study was obtained from UN Comtrade and the Central Statistics Agency (BPS) from 2006 to 2024. The methods used in this study include Revealed Symmetric Comparative Advantage (RSCA) and Export Competitiveness Index (ECI). The results show that the export performance of cocoa powder is relatively good, while that of chocolate is not so good. This is based on the RSCA and ECI values of cocoa powder, which are better than those of chocolate. The average RSCA value of cocoa powder is 0.62, while the average RSCA value of chocolate is -0.93. The average ECI value for cocoa powder is 0.95 and the average ECI value for chocolate is 0.97. One of the factors contributing to the good export performance of cocoa powder is that the export value of cocoa powder is higher than that of chocolate. Strict safety standards in export destination countries also pose a barrier to chocolate exports